Pengajaran Kursus Usul al-Fiqh Peringkat Ijazah Dasar Akademi Pengajian Islam, Universiti Malaya: Pengalaman dan Penilaian - Rahman, N.N.A.; Ali, A.K. (2006)
Teaching and learning of the principles of Islamic jurisprudence (U~iil al-Fiqh) is a part and parcel for shariah students in order to equip them with necessary tools to exercise their ability in carrying out legal deductions. However the established teaching method of U~iil al-Fiqh is questionable by certain scholars because it is claimed that it is incapable of producing "know-how" student in legal deduction and "ijtihad". Therefore, the article highlights a paradigm shift in teaching and learning of U~iil al-Fiqh with reference to the case of Academy of Islamic Studies, University of Malaya. The comparison between old and new subjects and syllabus is done. It is claimed that new subjects and approach will produce skill students in term of exercising "ijtihad" rather than knowing ijtihad. However the real achievement of student in this new curricula and subjects needs to be empirically proven.